Cohesion in L2 : Connectors as indicators of higher language competence - Dražić, Marija (2005)
Cohesion is one of the most important prerequisites of fluent text (or speech). There are considered to be four common types of cohesion: reference, ellipsis, conjunction (cohesion using connectors) and lexical cohesion. Our research examines the usage of connectors in randomly selected essays written by intermediate and advanced adult learners of Croatian as a foreign language. Cohesion by the use of connectors refers to the usage of specific words or phrases, usually at the beginning of a sentence in order to clarify the semantic or logical relationship of the information that follows with the information that has preceded it. By using cohesive items the semantic connection between sentences is much more specific and explicit. The appropriate usage of connectors in text demands a high level of language competence. Therefore we would like to show that lower language competence primarily results in the usage of reference as a cohesion type (usage of personal or demonstrative pronouns) and rare usage of connectors. On the contrary, advanced students use connectors more often, but often incorrectly. Some of the questions we would like to answer are: Is the usage of connectors a sign of high language competence? Is rare usage of connectors necessarily a sign of low language competence? What motivates the incorrect usage of connectors? What are the effects of incorrect usage of connectors on readers/listeners?